RATIONAL DRUG USAGE PATTERN OF STUDENTS AT UNIVERSITY OF COSTA RICA IN 2024 - Ortiz Ureña, Angie (2025)
Analyze the rational drug usage pattern of students at the University of Costa Rica, Rodrigo Facio campus, in 2024, by applying digital surveys as a data collection instrument, through on-campus visits and social networks. Results: It was noted that there was an increase in the access of medicines, independently, through pharmacies. Drug storage in the bedroom and in boxes was predominant. A major preference was found for purchasing medicines in physical pharmacies, with a growing interest in the use of virtual messaging platforms to acquire them. Most students follow medical directions when taking their medication. There are significant challenges in access, storage, use, and there is a recurring problem with inappropriate disposal of medications. Conclusion: Rational drug use pattern has evolved since a few years back, with changes observed such as an increase in use of digital platforms for buying medication since the pandemic, thanks to improved technological facilities that contribute to new forms of access. Significant challenges persist in self-medication and improper medication disposal.